A cross-country comparison on providing health services effectively during the first wave of COVID-19. (20th October 2021) - Webb, E; Hernández-Quevedo, C; Williams, G; Scarpetti, G; Reed, S; Panteli, D
Abstract: At the onset of the COVID-19 pandemic, health care providers had to abruptly change their way of providing care in order to simultaneously plan for and manage a rise of COVID-19 cases while maintaining essential health services. Even the most well-resourced health systems faced pressures from new challenges brought on by COVID-19, and every country had to make difficult choices about how to maintain access to essential care while treating a novel communicable disease. Using the information available on the HSRM platform from the early phases of the pandemic, we analyze how countries planned services for potential surge capacity, designed patient flows ensuring separation between COVID-19 and non-COVID-19 patients, and maintained routine services in both hospital and outpatient settings. Many country responses displayed striking similarities despite very real differences in the organization of health and care services. These include transitioning the management of COVID-19 mild cases from hospitals to outpatient settings, increasing the use of remote consultations, and cancelling or postponing non-urgent services during the height of the first wave. In the immediate future, countries will have to continue balancing care for COVID-19 and non-COVID-19 patients to minimize adverse health outcomes, ideally with supporting guidelines and COVID-19-specific care zones. Many countries expect to operate at lower capacity for routinely provided care, which will impact patient access and waiting times. Looking forward, policymakers will have to consider whether strategies adopted during the COVID-19 pandemic will become permanent features of care provision.